Peran Pengalaman Kerja dan Kompetensi terhadap Kinerja SDM Koperasi Pengelola Perkebunan Kelapa Sawit di Kabupaten Kotawaringin Barat - Mulyadi, Mulyadi (IAI Nasional Laa Roiba Bogor, 2025)
Cooperatives, as family-based business entities, play an important role in the economy and community welfare, with good HR performance being the key to sustainability and benefits for their members, especially in the agricultural sector. HR performance is influenced by competence and work experience, but research shows varying results regarding how significantly work experience affects performance, depending on the organizational context and type of work. The low level of understanding, experience, and education of cooperative administrators and employees in West Kotawaringin Regency resulted in only 19.76% of cooperatives actively holding Annual Member Meetings in 2023, indicating serious problems in HR performance that hinder the development and sustainability of cooperatives. This study aims to analyze the effect of work experience and competence on HR performance and the relationship between work experience and personal competence in cooperatives that manage oil palm plantations in West Kotawaringin Regency. This study will use Partial Least Square (PLS) data analysis, because this method is effective for testing relationships between variables without relying on the scale of measurement, sample size, or residual distribution. The results of the analysis show that the work experience variable explains 56.2% of the variation in HR performance, while the remaining 43.8% is influenced by other factors. In addition, work experience explains 22.5% of the variation in competence, while 77.5% is influenced by other factors outside the study. Work experience and competence have a positive and significant effect on the performance of cooperative HR, where work experience also improves the competence of cooperative administrators and managers.